An IgG4-Related Salivary Gland Disorder: A Case Series Presenting with a Different Clinical Setting - Masayuki Ishida; Hiroaki Fushiki; Yukio Watanabe (Case Reports in Immunology)
Küttner tumor is a chronic inflammatory disease that presents with a firm swelling of the submandibular gland and often mimics a neoplasm. Recently evidence suggests that Küttner tumor may be a type of disorder characterized by IgG4-related inflammations. Herein, we report 3 cases of submandibular gland swellings with severe fibrosis, inflammation with marked lymphoplasmacytic infiltration; this pathology mimics clinical manifestation of a malignant tumor in 18-fluorodeoxyglucose positron emission tomography (FDG-PET) findings.